The repetitive landscape of the 5100 Mbp barley genome - Wicker, Thomas; Schulman, Alan H.; Tanskanen, Jaakko; Spannagi, Manuel; Twardziok, Sven; Mascher, Martin; Springer, Nathan M.; Li, Qing; Waugh, Robbie; Li, Chengdao; Zhang, Guoping; Stein, Nils; et al. (My University, 2017)
Background: While transposable elements (TEs) comprise the bulk of plant genomic DNA, how they contribute to genome structure and organization is still poorly understood. Especially in large genomes where TEs make the majority of genomic DNA, it is still unclear whether TEs target specific chromosomal regions or whether they simply accumulate where they are best tolerated. Results: Here, we present an analysis of the repetitive fraction of the 5100 Mb barley genome, the largest angiosperm genome to have a near-complete sequence assembly. Genes make only about 2% of the genome, while over 80% is derived from TEs. The TE fraction is composed of at least 350 different families. However, 50% of the genome is comprised of only 15 high-copy TE families, while all other TE families are present in moderate or low copy numbers. We found that the barley genome is highly compartmentalized with different types of TEs occupying different chromosomal “niches”, such as distal, interstitial, or proximal regions of chromosome arms. Furthermore, gene space represents its own distinct genomic compartment that is enriched in small non-autonomous DNA transposons, suggesting that these TEs specifically target promoters and downstream regions. Furthermore, their presence in gene promoters is associated with decreased methylation levels. Conclusions: Our data show that TEs are major determinants of overall chromosome structure. We hypothesize that many of the the various chromosomal distribution patterns are the result of TE families targeting specific niches, rather than them accumulating where they have the least deleterious effects.